A palladium-catalyzed coupling reaction of aryl nonaflates, sulfur dioxide, and hydrazines. Issue 5 (24th December 2015) - An, Yuanyuan; Xia, Hongguang; Wu, Jie
Abstract : A facile route to synthesise N -aminosulfonamides through a palladium-catalyzed coupling reaction of aryl nonaflates, sulfur dioxide, and hydrazines is reported. This transformation proceeds in the presence of Pd(OAc)2 /XantPhos, and TBAB in 1, 4-dioxane at 80 °C, leading to the corresponding N -aminosulfonamides in moderate to good yields. Abstract : A facile route to synthesise N -aminosulfonamides through a palladium-catalyzed coupling reaction of aryl nonaflates, sulfur dioxide, and hydrazines is reported. This transformation proceeds in the presence of Pd(OAc)2 /XantPhos, and TBAB in 1, 4-dioxane at 80 °C, leading to the corresponding N -aminosulfonamides in moderate to good yields. The reaction scope has been demonstrated, and good functional tolerance is observed. A plausible mechanism is proposed through the insertion of sulfur dioxide.